Efeitos de interrupções na cadeia de impostos sobre valor adicionado: evidências em dados de declaração de ICMS no estado de São Paulo - Zulian, Bruno Lopau (2015)
Using data from the brazilian state of Sao Paulo on declarations regarding a VAT-like tax, the ICMS, I find that firms whose clients are enabled to use ICMS credits to offset their own tax liability – as in the standard VAT mechanism – present a lower evasion level than firms whose clients, due to enrollment on a special regime for small businesses, are not authorized by brazilian law to use the tax charged on their input purchases as credit, which, in a general setting, is representative of evidence on the existence of self-enforcent in value added taxes.